2010
DOI: 10.4066/amj.2010.362
|View full text |Cite
|
Sign up to set email alerts
|

A study on emergency contraceptive practice among nursing staff in Sikkim, India-A cross sectional study

Abstract: Background Improved knowledge about emergency contraception (EC) may decrease the unplanned pregnancy rate, unsafe abortion and save many lives. This study aims to assess the knowledge, attitude and practice of EC amongst the nursing staff in Sikkim. MethodThis study was carried out among 131 nursing staff in Gangtok between 2008 to 2009. A predesigned selfadministered questionnaire was used to collect the data. ResultsThe majority of nursing staff stated that they had heard of EC. About 80% gained knowledge a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 16 publications
0
17
1
Order By: Relevance
“…A similar study carried out in Sikkim reported that only 28% had actual knowledge on EC and 40% had a positive attitude towards EC [6]. In our study 30.81% of the participants were aware that EC was available OTC but 74% in the above study had awareness about its availability [6].…”
Section: Discussioncontrasting
confidence: 39%
“…A similar study carried out in Sikkim reported that only 28% had actual knowledge on EC and 40% had a positive attitude towards EC [6]. In our study 30.81% of the participants were aware that EC was available OTC but 74% in the above study had awareness about its availability [6].…”
Section: Discussioncontrasting
confidence: 39%
“…However, low levels of awareness of emergency contraception have been reported among nursing staff, and nursing students. 9,10 Access to emergency contraception is restricted by provider-related obstacles, such as, inadequate knowledge, prejudices, and limited distribution.…”
Section: Discussionmentioning
confidence: 99%
“…12 Not only clients, even health care providers do not have adequate and correct information, as reported in some studies. [13][14][15][16] If EC is used correctly and regularly, a large number of unwanted pregnancies after unprotected intercourse can be prevented. It is more valid in situations of contraceptive failure.…”
Section: Discussionmentioning
confidence: 99%